Ichthyoplankton Species Composition and Assemblages From the Estuary to the Hukou Section of the Changjiang River - Fang, Di-an; Xue, Xiang-ping; Xu, Dong-po; Wang, Xiao-hao; Sun, Ning-ze; Zhang, Bai-dong; Ren, Peng (Frontiers in Marine Science, 2021)
Estuary river–lake (ERL) complex is critical for the development of ichthyoplankton, which plays an essential role in the breeding, nursing, and recruitment of freshwater fish species. In this study, different ERL sections were selected to investigate the ichthyoplankton assemblage from the Changjiang River estuary to its Hukou section between May 2018 and August 2020. During the study period, fish larvae of 40, 35, 54, and 46 fish species were sampled in the Rugao (RG), Nanjing (NJ) (nearby estuary), Anqing (AQ), and Hukou (HK) (connected river–lake) sections in the Changjiang River, respectively. Results on ichthyoplankton surveys revealed fluctuating assemblage patterns in the different river sections; larval fish species composition presented ecological habitat-dependent characteristics, which supported the importance of ERL complex for ichthyoplankton development. Furthermore, the density of fish larvae was negatively correlated with water transparency but positively correlated with water temperature, the daily rate of water level increase, and runoff in the limitative range. A generalized additive model analysis indicated that the hydrological factors significantly affecting larval fish abundance are water temperature, transparency, the daily rate of water level increase, and runoff (p < 0.05). These results also indicated that river estuaries and river–lake connected complexes are essential for ichthyoplankton recruitment and migration. In combination with the historical record, ichthyoplankton assemblage’s patterns in the Changjiang River lower reaches were preliminarily elucidated, although additional works are needed such as assessing effects on their survival and recruitment.